1997
DOI: 10.1021/ja9618659
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity toward Dioxygen of Dicobalt Face-to-Face Diporphyrins in Aprotic Media. Experimental and Theoretical Aspects. Possible Mechanistic Implication in the Reduction of Dioxygen

Abstract: The reactivity toward dioxygen of two series of dicobalt cofacial diporphyrins in solution in an aprotic solvent is described. Some of these compounds are efficient electrocatalysts for the four-electron reduction of dioxygen when adsorbed on a graphite electrode immersed in aqueous acid. Their electrochemical and spectroscopic (UV−vis, EPR) behavior in solution shows that, contrary to what is observed with cobalt monomers, the neutral [PCoII CoIIP] (1) (P stands for a porphyrin ring) form does not react with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 88 publications
2
100
0
Order By: Relevance
“…However, quantitative calibration by double integration of the EPR signal of 2 + to a [Cu(acac) 2 ] standard reveals that this former complex is only a minor component of the mixture (< 10 %); presumably, 2 + is formed by initial oxidation of 1 to 1 + followed by dioxygen uptake. [5] No significant changes are observed in the 1 H NMR spectrum of 1 in CDCl 3 upon exposure to O 2 . However, the subsequent addition of [D 5 ]pyridine results in the observation of an NMR spectrum of the diamagnetic peroxido complex 2-py 2 .…”
Section: Comentioning
confidence: 94%
See 1 more Smart Citation
“…However, quantitative calibration by double integration of the EPR signal of 2 + to a [Cu(acac) 2 ] standard reveals that this former complex is only a minor component of the mixture (< 10 %); presumably, 2 + is formed by initial oxidation of 1 to 1 + followed by dioxygen uptake. [5] No significant changes are observed in the 1 H NMR spectrum of 1 in CDCl 3 upon exposure to O 2 . However, the subsequent addition of [D 5 ]pyridine results in the observation of an NMR spectrum of the diamagnetic peroxido complex 2-py 2 .…”
Section: Comentioning
confidence: 94%
“…[4,10,11] Plausible mechanistic pathways for both two-and four-electron reductions of dioxygen have also been elucidated. [1,2,5] [1,5] Significantly, neither of these modes has been corroborated by solidstate structural data for any dioxygen-containing cobalt diporphyrin complexes or porphyrinic analogues.…”
Section: (O C)(diporph)]mentioning
confidence: 96%
“…[13][14][15] In most cases, monomeric cobalt porphyrins catalyze the electroreduction of O 2 to hydrogen peroxide (H 2 O 2 ), whereas dimeric cofacial cobalt porphyrins demonstrate the catalysis of four-electron reduction of O 2 to water. [3,7,8,10,12,15,16,[24][25][26][27] Employing ferrocene derivatives as electron donors, O 2 reduction catalyzed by various cobalt porphyrins has been investigated by Fukuzumi et al in organic media in the presence of HClO 4 . [13][14][15] In the reaction scheme, the steps of electron coordination to form a superoxide adduct and its reduction by ferrocene derivatives to produce H 2 O 2 /H 2 O and Co III are fast, and that of reducing Co III by ferrocene derivatives is slow and rate limiting.…”
Section: Introductionmentioning
confidence: 99%
“…A new oxygen reduction mechanism has been proposed in the face-to-face cobalt porphyrin [8], in which the formation of a !-cation radical is a key factor in the coordination of oxygen to the metal site. Recently, a study reported that oxygen coordinates Fe(III) rather than Fe(II) to form an oxo dimer of Fe(IV) [9], although this study was conducted with a non-heme complex.…”
Section: Introductionmentioning
confidence: 99%